Simulation of Be armour cracking under ITER-like transient heat loads. (December 2016) - Pestchanyi, S.; Spilker, B.; Bazylev, B.
Highlights: We simulated beryllium cracking under action of multiple severe surface heating events using the PEGASUS-3D code. We used experiments in the JUDITH 1 facility for validation of the simulations. Analysis of the results has revealed beryllium thermo conductivity degradation under action of repetitive pulsed heat load due to accumulation of the cracks in the surface layer. Thermo conductivity degradation is found to be at least 4 times after 100 pulses in JUDITH 1 facility. An analytical model for the Be cracking threshold under action of arbitrary heat pulses has been developed. Abstract: Simulation of beryllium cracking under action of multiple severe surface heatings has been performed using the PEGASUS-3D code and verified by experiments in the JUDITH 1 facility. Analysis of the results has revealed beryllium thermo conductivity degradation under action of repetitive pulsed heat load due to accumulation of the cracks in the surface layer. Thermo conductivity degradation is found to be at least 4 times after 100 pulses in JUDITH 1 facility. An analytical model for the Be cracking threshold under action of arbitrary heat pulses has been developed.